The influence of sales growth and capital intensity on tax aggressiveness with inventory intensity as a moderating variabel - Bahtiar, Bahtiar; Wenten, I Ketut (Educoretax, 2024)
This research aims to empirically prove the influence of sales growth and capital intensity on tax aggressiveness, with inventory intensity as a moderating variable. The independent variables used in this research are sales growth and capital intensity, while the dependent variable is tax aggressiveness, and inventory intensity serves as the moderating variable. The population of this research consists of Consumers Non-Cylicals sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. The sample selection method is purposive sampling, yielding 12 companies or 60 observation samples. The data used are secondary data in the form of audited annual financial statements of each company. This research use Quantitative data analysis methods and associative problem formulation methods with causal relationships are used with the aid of E-views 12 software. The results indicate that sales growth and capital intensity simultaneously effect on tax aggressiveness. Partially, sales growth has a effect on tax aggressiveness, while capital intensity does not have a effect on tax aggressiviness. Additionally, the results indicate that inventory intensity does not moderate (weaken) the effect of sales growth on tax aggressiveness, nor does it moderate (weaken) the effect of capital intensity on tax aggressiveness.